Definition of the Bradysia luctifica group (Diptera, Sciaridae), with the description of five new species - Vilkamaa, Pekka; Suuronen, Anna (Zootaxa, 2019)
The Bradysia luctifica group is characterized for a number of species with an Oriental-Australasian distribution. The group includes the following species: Bradysia abrupta sp. n. (Malaysia: Pahang, Selangor), B. calicula sp. n. (Malaysia: Sabah), B. conflexa sp. n. (Malaysia: Pahang), B. fornicata sp. n. (Malaysia: Pahang), B. luctifica (Skuse, 1888) (Australia: South Australia, Indonesia: Ceram, New Caledonia, Papua New Guinea), B. robusta Mohrig, 2015 (Papua New Guinea) and B. torosa sp. n. (Papua New Guinea: Bismarck Archipelago). The species are keyed and the new species are described and illustrated.